Tendense in teologiese opieiding: Die pad vorentoe - Oberholzer, J. P. (Hervormde teologiese studies, 1994)
Trends in theological education: The road ahead From the viewpoint of ‘theology in the church for the church’, theology is typified as academic, ecclesiastical, universal, contextual and hermeneutical. Attention is drawn to the contemporary definition of a university, and to its emphasis on excellence and rationalisation, the demand both for theological freedom in the church and a curriculum projected towards man in the presence of God, on ecumenism as a disRosition of faith, the existential insecurity of man and the demand for theological relevance as well as eschatological expectation, theology as a complete discipline and the interpretation of message and context as a unitary act. Finally, some contemporary issues are indicated.